Hombres ciegos, ídolos huecos: fetichismo y alteridad en la crítica de la idolatría en el Apocalipsis de Abrahán - Hernández Valencia, Juan Sebastián (Universidad Católica Luis Amigó, 2023)
This work addresses the issue of idolatry through the questions posed in the Apocalypse of Abraham. While this issue is almost a common theme in the critique of Hebrew prophecy against the metaphysics of power structures, shining with originality, the critique in the Apocalypse of Abraham also offers a novel and lesser-known philosophical approach in theological and philosophical studies. The strategy developed in this research involves analyzing this critique through the appropriation of the concept of fetishism and from the perspective of Marxist ideology critique. Thus, this book presents a dialogue between exegesis and philosophy within the context of the issues and considerations of Latin American theology, drawing from a literature that is rarely studied in this context, such as that of Second Temple Judaism.